PENGARUH KOMBINASI EKSTRAK PARE (MOMORDICA CHARANTIA) DAN SAWO (MANILKARA ZAPOTA) TERHADAP PERTUMBUHAN BAKTERI SALMONELLA TYPHI SECARA INVIVO PADA USUS HALUS TIKUS - Awaluddin Susanto; Sri Sayekti (Jurnal Insan Cendekia, 2018)
Salmonella typhi bacteria is a main cause of typhoid fever. The fever can be healed by using medical and traditional way. Bitter melon plantand Sapodilla have a lot of active compound, having potential as antimicroba as like salmonella typhi. The problem of this research is to find out whether the extract combination of bitter melon and sapodillais effective in inhibitingthe growing of Salmonella typhi in mice small intestine. Thisresearch aims to determine inhibitory concentration in the growing of Salmonella typhi in mice small intestine. This researchused experimental design with post test group. This research used experimental animals that is mice which is given Salmonella typhi and is given the extract of bitter melon and sapodilla in different kinds of concentration with sonde. The measurement of bacteria is first by taking small intestine mucosa and put it SSA media. Then, it is being identified and accounted. After that, the data result is being tested by ANOVA with the data requirement that is normally distributed and homogeneous by using SPSS with α=0.05 The research result shows that there is 300 groups in positive control, while on the other way there is no groups found, except in 100% bitter melon group of seven bacteria groups. After being tested, the data shows that the score is not normal (sig. 0.000 < α =0.005). As the result, the data is being tested by using non parametric test and Kruskal-wallis test. Lastly, the test result shows there is a significant difference among treatment groups (sig. 0.013 < α =0.05) This research concludes that the combination extract of bitter melon and sapodilla effectively can inhibit the growing of Salmonella typhi by using in vivo in the mice small intestine.